2020
DOI: 10.1016/j.thromres.2020.08.017
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 versus HIT hypercoagulability

Abstract: A striking feature of COVID-19 is the high frequency of thrombosis, particularly in patients who require admission to intensive care unit because of respiratory complications (pneumonia/adult respiratory distress syndrome). The spectrum of thrombotic events is wide, including in situ pulmonary thrombosis, deep-vein thrombosis and associated pulmonary embolism, as well as arterial thrombotic events (stroke, myocardial infarction, limb artery thrombosis). Unusual thrombotic events have also been reported, e.g., … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
62
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(64 citation statements)
references
References 129 publications
(230 reference statements)
1
62
0
1
Order By: Relevance
“…This may be attributed to the increased exposure to heparin based thromboprophylaxis, increased hospital length of stay, and the hyperin ammation and heightened immune response in COVID-19 patients. 14,22,23 Diagnosing HIT is complex and requires 4Ts score calculation, EIA testing, and functional assay testing like SRA. 18 Our data, supported by the literature analysis, showed that 4Ts score was not predictive of either EIA + or patient mortality.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This may be attributed to the increased exposure to heparin based thromboprophylaxis, increased hospital length of stay, and the hyperin ammation and heightened immune response in COVID-19 patients. 14,22,23 Diagnosing HIT is complex and requires 4Ts score calculation, EIA testing, and functional assay testing like SRA. 18 Our data, supported by the literature analysis, showed that 4Ts score was not predictive of either EIA + or patient mortality.…”
Section: Discussionmentioning
confidence: 99%
“…11,12 Many COVID-19 patients have prolonged hospital stays leading to extended duration of heparin exposure, which increases risk for heparin induced thrombocytopenia (HIT). 13,14 HIT occurs when IgG antibodies form against platelet factor 4-Heparin complex, resulting in platelet activation, subsequently leading to a prothrombotic state. 15,16 HIT is suspected when there is a platelet count decrease of more than 50% after 5-10 days of heparin exposure, along with evidence of hypercoagulability.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…127,135,136 Some patients may suddenly deteriorate as a consequence of thromboembolism of large blood vessels, including pulmonary embolism. 137 In this setting, some robust, though preliminary, evidence indicates that low molecular weight heparin helps to prevent and treat this hypercoagulation syndrome. 138 To counter the systemic inflammation cascade before it causes multiorgan failure and death, therapy hinges on the use of immunomodulatory agents.…”
Section: Clinical Findings and Outcomes Of Covid-19mentioning
confidence: 99%
“…One of the explanations is the hypercoagulation state, due to rises in interleukin-6 (IL-6) and C reactive protein (CRP) levels [7]. Evidence of coagulation abnormalities has been observed in some patients with COVID-19, including thrombocytosis, hyperfibrinogenemia, elevated prothrombin time (PT) and partial thromboplastin time (PTT), elevated fibrin D-dimer, and elevated von Willebrand factor levels [8]. Cardiac and peripheral arteries, as well as cerebral arteries, are at risk for thrombosis.…”
Section: Introductionmentioning
confidence: 99%